Hubungan Antara Employee Learning, Knowledge, Creativity, Satisfaction, Benefits, Performance Terhadap Career Growth dan Turnover Karyawan. - Gilang Pratama Hafidz; Az-Zahra Al-May (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Career growth has an important role in human resource design strategies to achieve productivity, maintain retention, and improve company image. The purpose of this study is to determine the effect of employee learning, knowledge, creativity, satisfaction, benefits, and performance on career growth and employee turnover intention. Further factors can be seen in the variables of employee learning, employee knowledge, employee creativity, employee satisfaction, employee benefits, employee performance, career growth and turnover intention. This research use quantitative methods with purposive sampling technique distributed through questionnaires to 260 respondents in the Quality Control department employees in the footwear industry located in the JABODETABEK area. Primary data analysis was carried out using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method. The results of this study show that employee learning variables are found to have a role in determining the level of employee knowledge, employee creativity, and employee performance positively. Employee creativity has significant positive effect on employee satisfaction. Employee benefits have significant positive effect on employee satisfaction. Employee benefits have negative effect on employee performance. Employee knowledge has significant positive effect on employee performance. Employee satisfaction has significant positive effect on employee performance. Employee performance has significant positive impact on career growth. Career growth has negative effect on turnover intention. Next, in providing an intermediary impact, employee knowledge has impact between employee learning and employee performance. Employee benefits have impact between employee satisfaction and employee performance. This research is expected to contributes to the company for important implications in terms of company efficiency and productivity. The results of this study suggest to future researchers to expand the scope of sampling and extend the duration of the study.